Synthesis of equal-sized Y2O3:Bi, Eu mono-spheres and their color-tunable photoluminescence and thermal quenching properties. Issue 15 (15th October 2018) - Ma, Chang; Li, Xiaodong; Zhang, Mu; Liu, Shaohong; Li, Ji-Guang; Sun, Xudong
Abstract: On the basis of the synthesized equal-sized mono-spheres ( 180 nm), the luminescence properties of Y2 O3 :0.2 mol%Bi, 2 x mol%Eu ( x = 0.1–7) phosphors were investigated in detail. The PL spectra of Y2 O3 :Bi, Eu mono-spheres displays both the bluish green/blue emission of Bi 3+ at 501/410 nm ( 3 P1 - 1 S0, Bi 3+ in C2 or S6 sites) and the red emission of Eu 3+ at 612 nm ( 5 D0 – 7 F2 ) upon 330/375 nm excitation. Increasing the doping concentration of Eu 3+ ions in the phosphor mono-spheres significantly enhances Eu 3+ emission ( 5 D0 – 7 F2 ) and reduces Bi 3+ emission ( 3 P1 - 1 S0 ) due to the effective energy transfer from Bi 3+ to Eu 3+ ions. At the optimal Eu 3+ concentration of 3 mol%, the Y2 O3 :Bi, Eu mono-spheres show an intense red emission and a high external quantum efficiency of 42.8%. The energy transfer (ET) process from Bi 3+ to Eu 3+ ions is determined to be a resonant type via dipole-quadrupole interaction with an ET efficiency of 86.3%. By varying the Eu 3+ concentration, the luminescence color can be tuned from bluish green to nearly white and eventually to orange red under 330 nm excitation (Bi 3+ in C2 sites), and also can be tuned from blue to pink and then to orange red under 375 nm excitation (Bi 3+ in S6 sites). Temperature-dependent luminescence spectra demonstrated the good thermal stability of the obtained phosphor mono-spheres.